Vortioxetine exhibits anti-glioblastoma activity via the PI3K-Akt signaling pathway - Huan-Qi Zhang; Dao-Ming Zhang; Zhi-Zhen Huang; Jing Cheng; Chong Zhang; Neng-Ming Lin; Yang-Ling Li (Iranian Journal of Basic Medical Sciences)
Objective(s): Glioblastoma multiforme (GBM) presents a significant challenge in oncology due to its highly aggressive nature and inherent resistance to conventional therapeutic interventions. Vortioxetine, a novel antidepressant, exhibits anticancer abilities and can traverse the blood-brain barrier. In this study, the antitumor effect and mechanism of vortioxetine on GBM cells were investigated.Materials and Methods: Cell proliferation in GBM cells was assessed using the CCK8 and colony formation assays. Flow cytometry, western blot, and wound healing assay were used to study the mechanisms of vortioxetine. mCherry-GFP-LC3B and confocal microscopy were used to evaluate autophagic activity. RNA sequencing uses the capabilities of high-throughput sequencing methods to provide insight into the transcriptome of cells.Results: Vortioxetine significantly inhibited the proliferation of GBM cells by inducing G1/G0 phase cell cycle arrest. Meanwhile, it also reduced the migratory capabilities of GBM cells. Furthermore, it promoted apoptotic cell death in GBM cells. In addition, it promoted autophagy in GBM cells, and autophagy inhibitors markedly enhanced its antiproliferative activities. Vortioxetine could down-regulate the expressions of PI3K and Akt, which were related to the occurrence and development of GBM. Conclusion: Our findings support the potential of vortioxetine as a novel therapeutic agent for GBM treatment. Vortioxetine exhibits anti-GBM activity via the PI3K-Akt signaling pathway. Meanwhile, our findings reveal autophagy inhibitors as an effective sensitizer for vortioxetine, offering new strategies for treating GBM.